Competition and benefit sharing in the Ferghana Valley: Soviet negotiations on transboundary small reservoir construction - Pak, M.; Wegerich, Kai (Brill, 2014)
While there has been a regional and international focus on large reservoirs in Central Asia, smaller transboundary reservoirs within the Ferghana Valley have been overlooked. The valley is shared by Kyrgyzstan, Tajikistan, and Uzbekistan, three riparian countries of the upstream Syr Darya. Located within the valley are many small transboundary tributaries and reservoirs. An analysis of the initial proposals and documented negotiations for four of these reservoirs reveals a changing pattern of benefit sharing. These past approaches call into question the argument that the boundaries set by the Soviets did not matter, as well as the assumption that Moscow as a hegemon planned infrastructure in order to divide and rule Central Asia.